Participation of AD students in the Short Film Workshop & Sarawak Youth Short Film Education and Competition in conjuction with AIFFA 2017 - Mohd Fadil, Mohd Zaki; Sulaiman, Sumayyah (Universiti Teknologi MARA, Sarawak, 2017)
The soft launching of the Asean International Film Festival Award 2017 (AIFF.A2017) was held in Kuching on 16 February 2017 at Dewan Asajaya, Grand Margherita, Kuching to announce the upcoming film festival from 4 to 6 May 2017. In conjunction with the soft launching, a one-day Short Film Workshop organized by the Film Producers’ Association Malaysia was held on 16 February, 2017. The workshop was conducted by Datuk Paduka Shuhaimi Baba and Vaneeda Imran. Out of the 50 students and graduates from universities and colleges around Kuching attending the soft launching and workshop, 12 were the Faculty of Art & Design UiTM Sarawak students.